X-ray vision: mental representation of the human body’s inner morphology - Dias, Maria do Rosário; Neves, Ana Cristina; Simões, Nádia Pereira; Evangelista, José Grillo; Martins dos Santos, José (IJCR, 2016)
"The present study examines how undergraduate students of Health Sciences represent the human body inner morphology. A quantitative- and qualitative-based longitudinal study was conducted where 123 health sciences students were asked to draw the inner morphology of a Healthy Person and of a Sick Person in two separate moments: (i) before and (ii) after taking a Human Anatomy course unit. Those drawings were evaluated according to a content analysis matrix specifically designed for the purposes of the current research. A comparative analysis (before vs after academic training) of the collected data suggests atypicality of contents and a differential approach to the inner body at the structural anatomy level. Overall, Healthy Person representations show considerable younger individuals than those found in Sick Person representations. In most drawings, the body outline, which would represent the human body’s largest organ (the skin), is absent. Drawings also show a desexualization of the depicted bodies, for both representation types (healthy vs sick) failed to include reproductive organs. The pathologies most frequently portrayed in Sick Person representations were neoplasms of specific organs. Interestingly, the damaged organs were highly invested pictorially, in contrast with the lesser investment and amount of accessory organs depicted in Healthy Person representations."
This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Representation of the human inner body; Healthy person; Sick person; Undergraduate students of health sciences